Influence of anthropogenic landscape modifications and infrastructure on the geological characteristics of liquefaction. (March 2020) - Borella, Josh; Quigley, Mark; Riley, Moses; Trutner, Sarah; Jol, Harry; Borella, Maxwell; Hampton, Sam; Gravley, Darren
Abstract: Many large cities worldwide are built on natural and engineered geological materials that are highly susceptible to liquefaction and associated ground failure in earthquakes. Constitutive equations describing relationships between sediment geotechnical characteristics, seismological parameters, and liquefaction susceptibility of natural and engineered sediments are well established. What is less understood is the role of anthropogenic landscape modifications (e.g., river channel modifications, sediment engineering and re-distribution) and infrastructure (e.g., buildings, buried infrastructure such as drainage systems) on the spatial distributions and severity of liquefaction and ground deformation. Here we use stratigraphic studies, ground penetrating radar (GPR), and analyses of high-resolution aerial photographs to evaluate surface and subsurface geological manifestations of recurrent liquefaction in anthropogenically-modified landscapes during the 2010–2011 Canterbury earthquake sequence in New Zealand. Engineered fill layers provided low density, high permeability traps that captured fluidized sediment and promoted the formation of a unique assemblage of liquefaction-induced sediment intrusions that differ from those preserved in proximal natural sediment. Subsurface drainage systems imparted significant influence on the location, size and orientations of liquefaction ejecta features. Sediments adjacent to engineered stream channels experienced large lateral strains that are unlikely to have occurred in the absence of channel modifications. Spatial variations in naturally-formed topography and liquefaction-susceptible sediments exerted strong influence on the characteristics of liquefaction hazards, even in highly engineered environments. Collectively, these observations highlight important interactions between natural and engineered environments that should be carefully considered when interpreting the geologic effects of contemporary earthquakes and / or using prehistoric geological records to forecast future hazards.